PROMOSI, KETIDAKPUASAN KONSUMEN, DAN KEBUTUHAN MENCARI VARIASI TERHADAP MEREK PIXY KOTA BEKASI - Inas Afifah Zahra; Silfi Syahra Dewi (LPPM STIE Bisnis Internasional Indonesia, 2021)
This study aims to analyze the Influence of Promotion, Consumer Dissatisfaction and The Need to Find Variations in Brand Switching Behavior. The type of research is quantitative. The sampling technique used is accidental sampling with a total sample of 150 respondents. The method of data analysis used is descriptive. The Statistical analysis techniques used is SPSS 26 program with linear multiple regression statistical formula, simultaneous significance test (F-test), partial significance test (T-test) and coefficient of determination (R2). The results of the research statistics test showed the sig values < α (0.000 < 0.05) and F count > F tables or 75,621 > 2.74 at a significance level of 5% and R Square is 0.600 which means the promotion, the consumer dissatisfaction, and the need to find variations influenced in brand switching behavior.